1989
DOI: 10.1002/1097-0142(19890515)63:10<1927::aid-cncr2820631010>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Four-day continuous infusion of cisplatin and 5-fluorouracil in head and neck cancer

Abstract: A combination of cisplatin and 5-fluorouracil, both administered 4 days continuously as infusion, was assessed in advanced head and neck cancer. Of the 37 patients studied, there were 15 complete and 17 partial responses (40.5% and 45.9%, respectively). Survival is 79.1% at 22 months. None of the patients in complete response has relapsed. In general toxic effects were moderate. Given as initial treatment, the regimen is effective and of considerable use in this type of patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 18 publications
1
8
0
2
Order By: Relevance
“…It has been observed that continuous infusion of CDDP decreases nephrotoxicity probably by reducing peak level^.^^,^^ In consideration of the anticancer effect of such a dose schedule, it should be pointed out that Drewinko observed that CDDP cytotoxicity was enhanced by prolonged exposure of malignant cells to the Thus, Bernal et al used a 4-day continuous infusion of cisplatin and 5-fluorouracil in head and neck cancers and observed a response rate of 86% with 40.5% clinically complete responses. 36 These results are similar to those observed in regimens with boluses of cisplatin and continuous infusion of 5-Fluoro~raci1.~'-~~ In our study, in which the regimen of Bernal et al was used, 14% of patients showed a clear subclinical impairment of proprioceptive sensory fibers. We conclude that in chemotherapy regimens in which continuous infusion of CDDP was used without addition of another neurotoxic, the risk for peripheral nerve side effects is low up to a total dose of 300 mg/m2.…”
supporting
confidence: 88%
“…It has been observed that continuous infusion of CDDP decreases nephrotoxicity probably by reducing peak level^.^^,^^ In consideration of the anticancer effect of such a dose schedule, it should be pointed out that Drewinko observed that CDDP cytotoxicity was enhanced by prolonged exposure of malignant cells to the Thus, Bernal et al used a 4-day continuous infusion of cisplatin and 5-fluorouracil in head and neck cancers and observed a response rate of 86% with 40.5% clinically complete responses. 36 These results are similar to those observed in regimens with boluses of cisplatin and continuous infusion of 5-Fluoro~raci1.~'-~~ In our study, in which the regimen of Bernal et al was used, 14% of patients showed a clear subclinical impairment of proprioceptive sensory fibers. We conclude that in chemotherapy regimens in which continuous infusion of CDDP was used without addition of another neurotoxic, the risk for peripheral nerve side effects is low up to a total dose of 300 mg/m2.…”
supporting
confidence: 88%
“…Although a variety of chemotherapeutic agents have been employed in the past but the debate to optimize the drugs and the protocol is far from over. Combination of cisplatin with 5-FU has been widely used and investigated in induction chemotherapy settings, with high response rates but comparing with other chemotherapeutic drugs it has severe adverse effects especially mucositis (AlKourainy et al, 1987;Al-Sarraf et al, 1988;Bernal et al, 1989). In our study group all the patients responded to the induction chemotherapy with as high as 15% complete responders.…”
Section: Discussionmentioning
confidence: 99%
“…Postradiation or postoperative adjuvant chemotherapy seldom is tried because compromised vasculature, caused by radiation change or ablative surgery, will reduce drug penetration and the effectiveness of chemotherapy. The majority of clinical trials involve either neoadjuvant or concomitant chemotherapy for advanced SCCHN 3–6, 9–45. In general, the disadvantages of neoadjuvant chemotherapy include delayed primary treatment in nonresponders, refusal of further curative therapy in responders, triggering of accelerated repopulation of surviving clonogens,48 and cross‐resistance to further radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Oncologists have sought to improve local control and survival by combining chemotherapy with standard treatment in patients with advanced solid tumors 7–10. Both neoadjuvant chemotherapy (before surgery or radiotherapy) and concomitant chemotherapy (with radiotherapy) for head and neck tumors have been studied extensively during recent years 3–6, 9–45. However, there still is great controversy regarding the optimal timing, dosage, and contribution of chemotherapy to increase curability.…”
mentioning
confidence: 99%